TEST OF BURN HEALING ACTIVITY OF TIBARAU ROOT FRACTION (Saccaharum spontaneum L.) IN MALE WHITE MICE - rahmi, miftahur; Ria Afrianti; Wahilman Syahmi; Anggari Zulfian Siregar (JURNAL KATALISATOR, 2024)
Reed root (Saccharum spontaneum L.) is thought to have very strong antioxidant and anti- inflammatory activity that can help the wound healing process. Burns are injuries caused by exposure to heat. This study aimed to determine the burn healing activity of the extract and fraction of reed root. Extraction and fractionation methods. A total of 18 male white mice were burned and treated using extracts and fractions at a concentration of 15% in the form of ointment, each 3 mice in 6 groups, namely 15% ethanol extract, 15% n-hexane fraction, 15% ethyl acetate fraction, 15% n- butanol fraction, positive control, and experimental comparison. The test parameters were the percentage of wound healing, epithelialization time, and histopathology. Visually the 15% n-Butanol fraction has the best anti-burn activity with the average percentage of wound healing on the 7th; 14th; and 21st days, respectively 66.24%; 88.48%; 99 ,98%; epithelialization time 14,33. Histopathology on day 21 showed dense collagen fiber density, complete epithelialization cells and many fibroblast cells. Calculations using the One-Way ANOVA SPSS 16.0 statistical test followed by Duncan's test stated (P<0.05) the 15% n-Butanol fraction group was significantly different from the 15% ethyl acetate fraction group, comparison, 15% ethanol extract, n-Hexane fraction 15 % and positive control. From these results, it was concluded that the 15% n-Butanol fraction had the best burn healing activity.